Treatment of a Complex Case of Scleromyxedema Using a Novel Intravenous Immunoglobulin Preparation - Anastasia Sophie Vollmer; Nadine Wiedenmayer; Julia K. Winkler; Alexander H. Enk (Karger Publishers, 2024)
Introduction: We provide a case report on a patient with scleromyxedema treated with high-dose intravenous immunoglobulins (IVIgs) who reported less fatigue and fewer headaches after transitioning to Yimmugo, a novel IVIg preparation. Scleromyxedema is a rare and chronic cutaneous mucinosis, frequently associated with monoclonal gammopathy and systemic complications, which may be life-threatening. The disease is characterized by papular eruptions and sclerosis of the skin. Treatment of scleromyxedema is challenging because of its unclear pathogenesis. High-dose IVIgs are a promising treatment option to improve cutaneous manifestations. Case Presentation: We present the case of a 57-year-old patient with scleromyxedema and monoclonal gammopathy with end-stage renal failure on hemodialysis (3 times a week). Stabilization of skin symptoms was finally achieved by high-dose IVIg therapy administered at 2 g per kg bodyweight distributed over 2 days every 3 weeks. However, disease stabilization came at the expense of flu-like side effects that significantly affected daily life. After transitioning to Yimmugo®, the patient reported an improved quality of life. Conclusion: Further follow-up is essential to conclusively evaluate effectiveness and tolerability of this novel IVIg preparation.